2020
DOI: 10.3389/fpsyg.2020.01678
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Mapping Reading and Writing Motivation in Third to Eight Graders: A Self-Determination Theory Perspective

Abstract: The twofold aim of this study was to substantiate the validity of the Self-Regulation Questionnaire-Reading Motivation and Self-Regulation Questionnaire-Writing Motivation for third to eight graders and to map motivational trends in elementary and secondary education students' academic and recreational reading and writing. More specifically, we adopted the innovative and coherent theoretical framework of the Self-Determination Theory to study qualitatively different motives for reading and writing and to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 68 publications
1
23
1
Order By: Relevance
“…In this case, the development of the need for reading can become a latent sign. In work [9] it is noted that the upbringing of an autonomous type of motivation is possible through the use of teaching methods that support the innate psychological needs of students. The authors distinguish three types of essential needs that manifest themselves in the learning environment: the need for autonomy, the need for competence, and the need for belonging to significant others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the development of the need for reading can become a latent sign. In work [9] it is noted that the upbringing of an autonomous type of motivation is possible through the use of teaching methods that support the innate psychological needs of students. The authors distinguish three types of essential needs that manifest themselves in the learning environment: the need for autonomy, the need for competence, and the need for belonging to significant others.…”
Section: Discussionmentioning
confidence: 99%
“…://doi.org/10.1051/e3sconf/202021018073 studies[7][8][9]16]. Moreover, L. Kavanagh claims that «Findings from large-scale assessments consistently show girls significantly outperforming boys on tests of reading achievement, and these gender differences transcend languages and cultures»[12, p.5].…”
mentioning
confidence: 99%
“…These results are puzzling and might be explained by specific characteristics of secondary school students. Their autonomous reading motivation declines after entering adolescence (De Smedt, Heirweg, Rogiers, & Merchie, 2020). Therefore, this might not be sufficient to stimulate their reading strategy use, resulting in a stronger and positive contribution of controlled reading motivation.…”
Section: Indirect Contribution Of Reading Motivationmentioning
confidence: 99%
“…Teaching them how to deliberately use a rich repertoire of reading comprehension strategies during reading is a promising avenue in light of enhancing their comprehension of texts (Duke et al, 2011;Rogiers et al, 2020). Moreover, students' autonomous reading motivation tends to decline when students enter adolescence (e.g., De Smedt et al, 2020) and their reading enjoyment is found strikingly low in Flanders (i.e., the Dutch speaking part of Belgium) in the last PISA cycle (De Meyer et al, 2020). Consequently, the aim of ProjectExpert is to foster students' reading comprehension, strategy use and motivation.…”
Section: Aimmentioning
confidence: 99%